Triple Disruption dan Percepatan Akselerasi Transformasi Digital di Desa: Studi Inovasi Kebijakan Smart Kampung di Banyuwangi - Yunas, Novy Setia; Hakim, Andy Ilman; Pohan, Ibnu Asqori (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2023)
This article is the result of research that offers a new perspective in looking at the development of innovation and digital transformation in public services in regional government through a Triple Disruption perspective. One of them is the Smart Kampung in Banyuwangi, where services to the community can run effectively and efficiently not only focused on the district center, but also evenly to the marginalized layers of society through a technological approach. So far, disruption has only been seen from a technological perspective, but in a world that is so dynamic, disruption develops in conditions affected by the presence of the past Covid 19 pandemic and the increasingly urgent need for a green economy. This research aims to….Research with this qualitative approach. This researchwill look at the role of government and community actors in encouraging digitalization efforts in the public sector, especially in villages and the effectiveness of Smart Kampung policy innovations in Banyuwangi in efforts to accelerate digitalization in villages in the Triple Disruption era.